Safety analyses of adalimumab (HUMIRA) in global clinical trials and US postmarketing surveillance of patients with rheumatoid arthritis. Issue 7 (26th January 2006) - Schiff, M H; Burmester, G R; Kent, J D; Pangan, A L; Kupper, H; Fitzpatrick, S B; Donovan, C
Abstract : Objective: To assess the safety of adalimumab in global clinical trials and postmarketing surveillance among patients with rheumatoid arthritis (RA). Methods: Safety data for adalimumab treated patients from randomised controlled trials, open label extensions, and two phase IIIb open label trials were analysed. In addition, postmarketing spontaneous reports of adverse events in the United States were collected following Food and Drug Administration approval of adalimumab on 31 December 2002. Results: As of 15 April 2005, the RA clinical trial safety database analysed covered 10 050 patients, representing 12 506 patient-years (PYs) of adalimumab exposure. The rate of serious infections, 5.1/100 PYs, was comparable to that reported on 31 August 2002 (4.9/100 PYs), and to published reports of RA populations naive to anti-tumour necrosis factor (TNF) therapy. Following implementation of tuberculosis (TB) screening in clinical trials, the rate of TB decreased. There were 34 cases of TB as of this analysis (0.27/100 PYs). The standardised incidence ratio for lymphoma was 3.19 (95% CI 1.78 to 5.26), consistent with the observed increased incidence in the general RA population. As of 30 June 2005, there were an estimated 78 522 PYs of exposure to adalimumab in the US postmarketing period. Seventeen TB cases were spontaneously reported (0.02/100 PYs) from the US. Rates of other postmarketing events of interest, such as congestive heart failure, systemic lupus erythematosus, opportunistic infections, blood dyscrasias, lymphomas, and demyelinating disease, support observations from clinical trials. Conclusion: Analyses of these data demonstrate that long term adalimumab treatment is generally safe and well tolerated in patients with RA.